17
$\begingroup$

Prove:

$$\int_0^\infty x^{2n} e^{-x^2}\mathrm dx=\frac{(2n)!}{2^{2n}n!}\frac{\sqrt{\pi}}{2}$$

Thanks!

$\endgroup$
1
  • 19
    $\begingroup$ Please don't post questions as commands ("Prove ____." "Show _____.") because it is considered rude. $\endgroup$
    – Tyler
    Mar 14, 2011 at 17:00

5 Answers 5

39
$\begingroup$

Alternatively, set $$I(\alpha) = \int_0^\infty e^{-\alpha x^2}\mathrm{d}x,$$ differentiate $n$ times with respect to $\alpha$ and evaluate at $\alpha = 1$.

EDIT: To spell things a little more out, this technique is known as Differentiation under the integral sign. Using the fact that $I(\alpha) =\frac12\sqrt{\frac{\pi}{\alpha}}$ and differentiating to obtain $$\frac{\mathrm{d}^n}{\mathrm{d}\alpha^n} I(\alpha) = (-1)^n\int_0^\infty x^{2n} e^{-\alpha x^2}\mathrm{d}x, $$ some algebraic manipulation and evaluating at $\alpha = 1$ will yield the wanted identity.

$\endgroup$
0
24
$\begingroup$

Alternatively, integration by parts works immediately.
Let $$a_n=\int_0^\infty x^{2n}e^{-x^2}.$$ Consider $U=x^{2n-1}$ so that $du=(2n-1)x^{2n-2}$, and $dv=xe^{-x^{2}}$ so that $V=-\frac{1}{2}e^{-x^{2}}$.

Then $$\int_{0}^{\infty}x^{2n}e^{-x^{2}}dx=\frac{1}{2}e^{-x^{2}}x^{2n-1}\biggr|_{0}^{\infty}-\int_{0}^{\infty}(2n-1)x^{2n-2}\frac{-1}{2}e^{-x^{2}}dx$$ $$=\frac{(2n-1)}{2}\int_{0}^{\infty}x^{2n-2}e^{-x^{2}}dx=\frac{(2n-1)2n}{2^{2}n}\int_{0}^{\infty}x^{2n-2}e^{-x^{2}}dx$$

Hence $$a_n=\frac{(2n)(2n-1)}{2^2n}a_{n-1}$$ and since $a_0=\frac{\sqrt{\pi}}{2}$ we conclude $$a_n=\int_{0}^{\infty}x^{2n}e^{-x^{2}}dx=\frac{(2n)!}{2^{2n}n!}\frac{\sqrt{\pi}}{2}$$ by induction.

Hope that helps,

$\endgroup$
12
$\begingroup$

Making a change of variable $u=x^2$ gives $$ \int_0^\infty {x^{2n} e^{ - x^2 } dx} = \frac{1}{2}\int_0^\infty {u^{n - 1/2} e^{ - u} du} = \frac{1}{2}\Gamma (n + 1/2). $$ Then from the well-known formula for the gamma function $$ \Gamma (n + 1/2) = \frac{{(2n)!}}{{4^n n!}}\sqrt \pi $$ we get $$ \int_0^\infty {x^{2n} e^{ - x^2 } dx} = \frac{{(2n)!}}{{2^{2n} n!}}\frac{{\sqrt \pi }}{2}. $$

Second approach. Writing $$ \int_0^\infty {x^{2n} e^{ - x^2 } dx} = \frac{1}{2} \frac{{\sqrt {2\pi (1/2)} }}{{\sqrt {2\pi (1/2)} }} \int_{ - \infty }^\infty {x^{2n} \exp \bigg( - \frac{{x^2 }}{{2(1/2)}}\bigg)dx} $$ shows that $$ \int_0^\infty {x^{2n} e^{ - x^2 } dx} = \frac{{\sqrt \pi }}{2}{\rm E}[X^{2n} ], $$ where ${\rm E}[X^{2n} ]$ is the $2n$-th moment of the Normal$(0,1/2)$ distribution. Now you can see how others, here for example, find ${\rm E}[X^{2n} ]$ (for a Normal$(0,\sigma^2)$ distribution). The simplest approach may be to use integration by parts. I'll leave it to you.

EDIT (in light of the OP's edit): Integration by parts gives the result, using induction, as follows: $$ \int_0^\infty {x^{2(n + 1)} e^{ - x^2 } dx} = \frac{{2n + 1}}{2}\int_0^\infty {x^{2n} e^{ - x^2 } dx} = \frac{{[2(n + 1)]!}}{{2^{2(n + 1)} (n + 1)!}}\frac{{\sqrt \pi }}{2}. $$ For the base case $n=0$, note that $\int_0^\infty {e^{ - x^2 } dx} = \frac{{\sqrt \pi }}{2}$.

$\endgroup$
10
$\begingroup$

Let's suppose that, one way or another, you know that $ \displaystyle \int_{-\infty}^{\infty} e^{-x^2} \, dx = \sqrt{\pi}$. Then

$$\int_{-\infty}^{\infty} e^{2tx - x^2} dx= e^{t^2} \int_{-\infty}^{\infty} e^{-(t - x)^2} \, dx = e^{t^2} \sqrt{\pi}.$$

On the other hand,

$$\int_{-\infty}^{\infty} e^{2tx - x^2} dx = \int_{-\infty}^{\infty} \left( \sum_{n \ge 0} \frac{2^n t^n x^n}{n!} \right) e^{-x^2} dx = \sum_{n \ge 0} \frac{2^n t^n}{n!} \int_{-\infty}^{\infty} x^n e^{-x^2} \, dx.$$

Finally, note that by evenness,

$$\int_{-\infty}^{\infty} x^{2n} e^{-x^2} \, dx = 2 \int_0^{\infty} x^{2n} e^{-x^2} \, dx.$$

$\endgroup$
2
  • $\begingroup$ Do you mean the integral from 0 to infinity? $\endgroup$
    – Raeder
    Mar 15, 2011 at 12:42
  • $\begingroup$ @Raeder: thank you for reminding me that I messed up the constant in the first statement, but no. The first step is messier if you take the integral from zero; you want the integral over the entire real line to get translational symmetry, but on the other hand $e^{-x^2}$ is even. $\endgroup$ Mar 15, 2011 at 12:45
1
$\begingroup$

Case 1: For $n=0$ we have $ \int^{\infty}_{0}{e^{-x^{2}}}dx=\frac{\sqrt{\pi}}{2}$. Now, we use the fact that $e^{-x^{2}}$ is an even function, and thus we have $\int^{\infty}_{0}{e^{-x^{2}}}dx=\frac{1}{2}\int^{+\infty}_{-\infty}{e^{-x^{2}}}dx. $ Moreover, $$\int^{+\infty}_{-\infty}{e^{-x^2}}dx = \sqrt{\left(\int^{+\infty}_{-\infty}{e^{-x^{2}}}dx\right)\left(\int^{+\infty}_{-\infty}{e^{-x^{2}}}dx\right)}=$$ $$= \sqrt{\left(\int^{+\infty}_{-\infty}{e^{-y^{2}}}dy\right)\left(\int^{+\infty}_{-\infty}{e^{-x^{2}}}dx\right)} = \sqrt{\int^{+\infty}_{-\infty}\int^{+\infty}_{-\infty}{e^{-\left(x^{2}+y^{2}\right)}}dydx}$$

Here, we use the fact that the variable in the integral is a dummy variable that is integrates out in the end and can be renamed from $x$ to $y$. Moreover, switching to polar coordinates then gives $$\int^{+\infty}_{-\infty}{e^{-x^{2}}}dx =\sqrt{\int^{2\pi}_{0}\int^{+\infty}_{0}e^{-r^{2}r}drd\theta} = $$ $$ =\sqrt{\int^{+\infty}_{0}re^{-r^{2}}\int^{2\pi}_{0}d\theta} = \sqrt{-\frac{1}{2}e^{-r^{2}}|^{\infty}_{0}\cdot 2\pi} = $$ $$ = \sqrt{\frac{1}{2}\cdot 2\pi} = \sqrt{\pi}$$
And so $\int^{\infty}_{0}{e^{-x^{2}}}dx=\frac{1}{2}\int^{+\infty}_{-\infty}{e^{-x^{2}}}dx=\frac{\sqrt{\pi}}{2}$.

Case 2: For $n\geq 1$. Let $a_n= \int^{+\infty}_{0}{x^{2n}e^{-x^{2}}}dx$. Using integration by parts, let $u_{1}=x^{2n-1}$ so that $du_{1}=(2n-1)x^{2n-2}dx$, and $dv_{1}=xe^{-x^{2}}dx$ so that $ v_{1}=-\frac{1}{2}e^{-x^{2}}$. Then $$\int^{+\infty}_{0}{x^{2n}e^{-x^{2}}}dx = -\frac{1}{2}e^{-x^{2}}x^{2n-1}|^{+\infty}_{0}-\int^{+\infty}_{0}{-\frac{1}{2}e^{-x^{2}}(2n-1)x^{2n-2}}dx =$$ $$ = 0+ \frac{(2n-1)}{2}\int^{+\infty}_{0}{x^{2n-2}e^{-x^{2}}}dx = \frac{(2n-1)}{2}\int^{+\infty}_{0}{x^{2n-2}e^{-x^{2}}}dx$$

Using the integration by parts again, we let $u_{2}=x^{2n-3}$ so that $du_{2}=(2n-3)x^{2n-4}dx$, and let $dv_{2}=xe^{-x^{2}}dx$ so that $v_{2}= -\frac{1}{2}e^{-x^{2}}$. Again we have $$ \int^{+\infty}_{0}{x^{2n}e^{-x^{2}}}dx = \frac{(2n-1)}{2}\int^{+\infty}_{0}{x^{2n-2}e^{-x^{2}}}dx =$$ $$ = \frac{(2n-1)}{2} \left(-\frac{1}{2}x^{2n-3}e^{-x^{2}}-\int^{+\infty}_{0}{-\frac{1}{2}e^{-x^{2}}(2n-3)x^{2n-4}dx}\right) = \frac{(2n-1)}{2} \left(0-\int^{+\infty}_{0}{-\frac{1}{2}e^{-x^{2}}(2n-3)x^{2n-4}dx}\right) =$$ $$ = \frac{(2n-1)(2n-3)}{2^{2}} \int^{+\infty}_{0}{e^{-x^{2}}x^{2n-4}dx}$$ Following the same process, we can obtain $$a_n = \int^{+\infty}_{0}{x^{2n}e^{-x^{2}}}dx = \frac{(2n-1)(2n-3)(2n-5)(2n-7)\ldots (7)(5)(3)(1)}{2^{n}}\cdot a_{0} =$$ $$ =\frac{(2n-1)(2n-3)(2n-5)\ldots(5)(3)(1)}{2^{n}}\cdot a_{0}\cdot\left(\frac{(2n-2)(2n-4)(2n-6)\ldots(6)(4)(2)}{(2n-2)(2n-4)(2n-6)\ldots(6)(4)(2)}\right) = \frac{(2n-1)(2n-3)(2n-5)\ldots(5)(3)(1)}{2^{n}}\cdot a_{0}\cdot \frac{(2n-2)(2n-4)(2n-6)\ldots(6)(4)(2)}{2^{n-1}(n-1)(n-2)(n-3)\ldots(3)(2)(1)} = $$ $$ = \frac{(2n-1)(2n-2)(2n-3)\ldots (3)(2)(1)}{2^{n}2^{n-1}(n-1)!}\cdot a_{0} = \frac{(2n-1)!}{2^{2n-1}(n-1)!}\cdot a_{0} = $$ $$ = \frac{(2n-1)!}{2^{2n-1}(n-1)!}\cdot\frac{2n}{2n}\cdot a_{0} = \frac{(2n)!}{2^{2n-1}2(n-1)!n}\cdot a_{0} = $$ $$ = \frac{(2n)!}{2^{2n}(n)!}\cdot a_{0} = \frac{(2n)!}{2^{2n}(n)!}\cdot \frac{\sqrt{\pi}}{2}$$ from Case 1.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.